2022
DOI: 10.3389/fphar.2022.838079
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Cancer: From the Development of Personalized Indicators to Novel Therapeutic Strategies

Abstract: Colorectal (CRC) and hepatocellular carcinoma (HCC) are associated with chronic inflammation, which plays a role in tumor development and malignant progression. An unmet medical need in these settings is the availability of sensitive and specific noninvasive biomarkers. Their use will allow surveillance of high-risk populations, early detection, and monitoring of disease progression. Moreover, the characterization of specific fingerprints of patients with nonalcoholic fatty liver disease (NAFLD) without or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 167 publications
(235 reference statements)
0
18
0
1
Order By: Relevance
“…PGE2 plays various roles in cancer progression, including proliferation, migration, and immune escape. Tumor cells can acquire migratory capacity, which promotes metastatic colonization ( 50 ). Notably, ω-6 polyunsaturated fatty acids (PUFAs) were found to enhance the metastatic potential of gastric cancer cells via COX-2/PGE2 ( 51 , 52 ).…”
Section: The Role Played By Cyclooxygenase-2 In Different Diseasesmentioning
confidence: 99%
“…PGE2 plays various roles in cancer progression, including proliferation, migration, and immune escape. Tumor cells can acquire migratory capacity, which promotes metastatic colonization ( 50 ). Notably, ω-6 polyunsaturated fatty acids (PUFAs) were found to enhance the metastatic potential of gastric cancer cells via COX-2/PGE2 ( 51 , 52 ).…”
Section: The Role Played By Cyclooxygenase-2 In Different Diseasesmentioning
confidence: 99%
“…Pliszczak-Król et al found that the platelet number was at its maximum in four-week-old piglets and reached its minimum at week 18 [ 14 ]. In general, a high platelet number is a sign of inflammation [ 15 , 16 ] and disease [ 17 ]. Thus, normal BPIs play a key role in pig health and growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, these defense reactions result in the development of pain, swelling, bruising, or redness. Whether the inflammatory process persists and leads to a chronic state that can cause severe damage to many tissues and is associated with developing serious diseases such as tissue fibrosis, atherosclerosis, and cancer ( Dovizio et al, 2017 ; Ballerini et al, 2022 ), depends on the ability or failure to induce resolution of the inflammatory process.…”
mentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is highly induced in inflammation-driven diseases such as colorectal cancer (CRC) ( Ballerini et al, 2022 ). Stamatakis et al showed that many genes expressed in the mouse colorectal cancer cell line CT26 are COX-2-regulated.…”
mentioning
confidence: 99%